'Put in a room and left': a qualitative study exploring the lived experiences of COVID-19 isolation and quarantine among rehabilitation inpatients. (31st December 2023) - Luker, Subbuh; Laver, Kate; Lane, Rachel; Potter, Elizabeth; Harrod, AnnMarie; Bierer, Petra; Adey-Wakeling, Zoe; Karnon, Jonathan; Cameron, Ian D.; Crotty, Maria
Abstract: Background: The SARS-CoV-2 (COVID-19) pandemic has resulted in significant changes to health care delivery and the patient's experience in hospital. Changes for those who contracted COVID-19 or were close contacts included isolation and quarantine, visitor restrictions and changes to usual models of care to reduce viral transmission. Traditional models of inpatient rehabilitation utilise communal spaces (e.g. shared gyms and dining rooms) and involve a multidisciplinary team interacting with the patient daily. Objectives: To report the experience of COVID-19 related isolation and quarantine among rehabilitation inpatients and their family members who experienced a nosocomial outbreak and to make recommendations for rehabilitation units. Methods: A qualitative phenomenological methodology using semi-structured telephone interviews. Results: 19 semi-structured interviews were conducted comprising of 13 general rehabilitation inpatients and 6 family members. Five themes were established: (1) the impact of social and physical isolation; (2) boredom and limited access to therapy; (3) the impact of technology; (4) inadequate information sharing and (5) positive experiences and things done well. Several novel insights were identified including: the desire for increased social interaction from staff to compensate for a lack of visitors; the impact of physical and cognitive deficits on a patient's ability to reach basic items around their room or call for help, and the unique impact of isolation and quarantine on individuals who have a history of trauma, discrimination or mental illness. Conclusions: This study establishes key areas that should be considered by rehabilitation units globally to adjust traditional models which are not suitable in this pandemic. Strategies to mitigate the impact of isolation include providing training to increase use of technologies such as tablet devices, increased staff social engagement to reduce isolation and tailoring the environment to suit specific patient groups. KEY MESSAGES: COVID-19 related isolation and quarantine has a significant and unique impact on patients with cognitive and physical impairments such as those in inpatient rehabilitation. Patients who are required to isolate in inpatient settings expressed a desire for compensatory increased social interaction from staff and required specific assistance with basic daily tasks while isolated. The study makes key recommendations for other rehabilitation units to integrate into their approach for managing patients required to isolate or quarantine.